ALAT UKUR TINGGI BADAN DENGAN DETEKSI ULTRASONIC SERTA INFORMASI BERBASIS DISPLAY DAN SUARA - Dadang Haryanto; Nanang Durahman (ADISAM PUBLISHER, 2025)
The development of technology today brings us to the digital era, so it greatly aflects human behaviour in their daily activities in completing their work, as most aspects of human life depend on technology, this can be marked by the increasing number of technologies used by humans in various fields, including in daily needs as a medium of information, technology was also created to facilitate and assist humans in completing various activities. Seeing the activities carried out by people today have led to digital behaviour along with the development of technology today brings us to the digital era, thus greatly aflecting human behaviour in their daily activities, almost all aspects of human life are technology-based which facilitates human activities in carrying out their work, this can be indicated by the increasing number of technologies used by humans in various fields, including in the needs of daily human work. Technology was also created to facilitate and assist humans in completing various activities. So it is hoped that the existence of digital technology can make it more comfortable and easier for humans to complete their work. Human height depends on environmental and genetic factors. The average growth for each sex in the population is significantly diflerent, with adult men being taller on average than adult women. To determine height, a measuring instrument called a height gauge is needed, which is usually expressed in units of CM or Inc. To measure height we can go to the clinic and ask the officer to do an examination, or do it yourself at home with the help of others.But sometimes, there are some urgent things that make us have to know our height immediately. Or even we are attacked by laziness when we want to do height control to the clinic.With the development of technology today, it is possible to take height measurements at home even without the help of others. So that it can make it easier for us to check our height. The output expected by the author in this research is the making of the Intellectual Property Rights (HAKI) process in the form of copyright and publishing this research in an accredited national journal and of course in implementation can be used by schools or health services